The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12894-022-01027-2
|View full text |Cite
|
Sign up to set email alerts
|

Metformin exerts an antitumor effect by inhibiting bladder cancer cell migration and growth, and promoting apoptosis through the PI3K/AKT/mTOR pathway

Abstract: Background To observe and explore the effect of metformin on the migration and proliferation of bladder cancer T24 and 5637 cells in vitro. Methods Bladder cancer T24 and 5637 cell lines were cultured in vitro, and were divided into group A (blank control group) and group B (metformin group: 5, 10, 15, and 20 mmol/L); both groups were plated on 6-well plates at the same time. Culture in 24-well plates was used for wound healing assays and in 96-wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Also, the induction of p53, BAX, cleaved PARP and cleaved caspase 3 along with a reduction in BCL-2 in HCC cells after metformin treatment was reported [103]. This proapoptotic profile induced by metformin was also observed in bladder cancer [107] and in osteosarcoma [108]. It was previously observed that metformin can reduce SURVIVIN levels through AMPK and the mechanistic target of rapamycin kinase (mTOR) axis [109].…”
Section: Cell Death Mechanisms Related To Metforminmentioning
confidence: 85%
“…Also, the induction of p53, BAX, cleaved PARP and cleaved caspase 3 along with a reduction in BCL-2 in HCC cells after metformin treatment was reported [103]. This proapoptotic profile induced by metformin was also observed in bladder cancer [107] and in osteosarcoma [108]. It was previously observed that metformin can reduce SURVIVIN levels through AMPK and the mechanistic target of rapamycin kinase (mTOR) axis [109].…”
Section: Cell Death Mechanisms Related To Metforminmentioning
confidence: 85%
“…Several preclinical studies in different cancer types have suggested that metformin may exhibit its antiproliferative effects through the inhibition of PI3K/AKT/mTOR. In bladder cancer cells, the biguanide in a concentration-dependent manner led to the reduction of PI3K, AKT, and mTOR phosphorylation and was ultimately associated with the suppression of cell proliferation and migration, the activation of the caspase cascade, and the induction of apoptosis [82]. In a study performed by Nozhat et al in anaplastic thyroid cancer (ATC) cell lines, metformin in a time-and dose-dependent way repressed cell growth, significantly altered ATC cellular morphology, and decreased cell migration, likely by reducing the mRNA expression of PI3K and AKT, with no impact, however, on their phosphorylation status [83].…”
Section: Direct Anticancer Mechanisms Of Metforminmentioning
confidence: 99%
“…18 A recent experimental study has shown that metformin exerts antitumour effect by inhibiting bladder cancer cell migration and growth and promoting apoptosis. 19…”
Section: Iatrogenic Bladder Dysfunction From Endocrine Drugsmentioning
confidence: 99%

The endocrinology of the urinary bladder

Saptarshi Bhattacharya,
Arbinder Kumar Singal,
Sanjay Kalra
2023
J Pak Med Assoc